Empowering Informal Learning and Soft-Skill Enrichment Through an Arts -based Project of Animation among Secondary School Students - Khir, Roselina; Pawanteh, Murina; Lajis, Ahmad S.; Stephens, John (Advances in Social Sciences Research Journal, 2022)
This research aimed to share with educational stake-holders how informal learning through an Arts -based project can contribute to soft-skill enrichment among school learners. The soft skills looked at were based on the 4 C -skills, Creativity, Critical Thinking, Communication and Collaboration. Secondary school students carried out an animation project based on a musical theatre during the Covid -19 pandemic, half of it online, and half through physical meetings. To achieve these objectives, this research used observation, self-reflection and questionnaires to collect data from 13 students and responses from 3 virtual critics. The analysis method used for this research was descriptive analysis. The results showed that specific arts ensemble activity such as creating a performance or animation is able to produce high level of generalized group production skills. The module can be used as indicators for future arts project collaboration with the 4C’s as the final outcome. These participants believed that an arts-based project had opened up their minds and outlook beyond school exams.